A constituição e o funcionamento do gênero jornalístico artigo: cronotopo e dialogismo - Rodrigues, Rosângela Hammes (2001)
This research aims at conducting an interpretive description of the constitution and functioning of the discursive genre "article", of the journalistic sphere. Its theoreticalmethodological background follows mainly Bakhtin's socio-historical approach of language and subject constitution: his concept of language, utterance, and discursive genres. The interpretive description of the article was carried out based upon the analysis of sixty two articles, published in the opinion section of four newspapers (two of nationwide and two of statewide circulation), collected once per month, between September, 1998 and March, 1999. The methodology for the analysis of the genre "article" was centered upon that proposed by Bakhtin: from the communicative social exchanges to the genre or language aspects, given that one cannot dissociate the sign from the concrete forms of social communication. In the context of this theoretical-methodological perspective, discursive genres have been considered as historical types of utterances, composed of two inextricable fundamental dimensions, namely, the social and the verbal. In the analysis of the social dimension, this research shows the peculiarities of its social sphere (ideological aim of journalism in the whole of social life, etc.), and the interaction situation of the article in that sphere: linkage to the opinion section, daily periodicity, classes A, B, C readers as addressees, authorship’s concept centered upon social status and media-criteria. The analysis of the verbal part leads to the conclusion that the "article" is characterized as a reaction-evaluative response of this author to current social events, which are of interest to the journalistic sphere. The appreciative-oriented production is constructed through the particular dialogic relationship of three enunciating instances: the author’s position, which functions as an authority’s argument, and its enunciating developments; the relationship with the already produced utterances, which the author approximates to or distances from his discourse (dialogic movements of assimilation and distancing), aiming at argumentative-oriented production; the relationship with the reader’s active reactionresponse, with the purpose of refuting objections, engaging him in his discourse and interpellating him vis-à-vis the adoption of a certain evaluative attitude (dialogic movements of engagement, refutation, and interpellation)